Some Effects of Fibrinogen Degradation Products (FDP) on Blood Platelets - Jerushalmy, Z; Zucker, M. B (Thrombosis and Haemostasis, 1966)
“Early” fibrinogen degradation products are more potent inhibitors of thrombin-induced clotting than “late” products and also interfere with the ability of thrombin to release serotonin from platelets. “Early” and “intermediate” FDP cause moderate inhibition of platelet aggregation induced by adenosine diphosphate or connective tissue particles. Serotonin release by connective tissue particles is probably not inhibited by FDP.